Social media and new norms impact : “Oh! My Grandparents (OMG)!” as an administrator in family whatsApp group - Azian Muhamad Adzmi; Liyana Mohd Ramly; Syahida Mohd Nazri; Nik Fatinah N. Mohd Farid; Muhammad Asyraf Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2021)
WhatsApp has become a major necessity in modern communication both individually and as a group. During an unprecedented time like COVID-19 pandemic, it increased the utilization of social media among society and has developed new norms among its users, especially grandparents. This study emphasises the various real-life activities undertaken by grandparents in social media and detailed research regarding the various WhatsApp administrators in a group chat. A qualitative research approach consisting of in-depth interviews have been carried out among family members in order to gather all the information-involving informants. In addition, it aims to gain a broader perspective of the informants' view regarding their grandparents becoming the administrator of a family WhatsApp group. Results of this study revealed that family relationships became strengthened between grandparents and other family members, especially with their grandchildren. Secondly, grandparents started being obsessed with WhatsApp, they are keen to learn more and are even able to keep up with the latest technology. Finally, the topics discussed in the family WhatsApp group covers current issues such as politics, religious advice, and sometimes entertainment. Generally, this study is expected to contribute to the communication studies and social media field, specifically understanding the use of social media between two different generations that are keen to keep up to date with the current technology especially during the unprecedented time.